PARENTAL INTENTION TO VACCINATE THEIR CHILDREN ABOUT COVID-19 VISITING A TERTIARY CARE HOSPITAL IN KARACHI, PAKISTAN - HUSSAIN , W; HALO , LA; SHAIKH, M; HANIF, M; PERVAIZ , S; PARKASH , A (Biological and Clinical Sciences Research Journal, 2023)
The SARS-CoV-2 virus is the source of the extremely contagious illness known as COVID-19. One of the most important ways to control the pandemic now is vaccination. However, vaccine reluctance exists in various communities due to false information and myths. This study evaluated parental readiness to vaccinate their children following the establishment of pediatric immunization recommendations. Parents who visited the National Institute of Child Health outpatient clinics in Karachi, Pakistan, were the subjects of a cross-sectional survey. Data on demographics, parental attitudes toward the COVID-19 vaccine, and parental readiness to administer it to their children were gathered by trained data collectors. A total of 341 parents participated in the study; the majority (47.2%) were female and between the ages of 31 and 40. Regarding the acceptability of immunizing their kids against COVID-19, 47.2% of parents said they would be willing to do so, while 27% said they would be reluctant. Lack of knowledge (95.5%) and a lack of supporting proof were the most often cited objections among those who declined (92.6 percent ). Parental age, notably between the ages of 31 and 40, and the age of their children, particularly between the ages of 4 and 12, were strongly linked with lower vaccine reluctance. The impacts of gender, marital status, or educational attainment were not statistically significant. A big part of stopping the spread of COVID-19 is vaccination. According to our research, the majority of parents are probably going to vaccinate their kids. The age of the kid and certain parent age groups (31–40 years old) were strongly linked to reduced vaccine reluctance. To increase vaccine acceptance rates among parents, addressing the lack of knowledge and evidence, which are the main causes of vaccine refusal, is critical.